The Social Position of Doctoral Candidates within the Academic Field: Comparative Considerations Regarding Doctoral Program Attrition in Germany and the USA - Franz, Anja (International Dialogues on Education Journal, 2015)
During the ongoing period of transformation of the German doctoral education from the individual master-apprentice model to more structured PhD programs, US-American PhD programs have served as a model for many of the newly established programs. One of the political aims of restructuring doctoral education in Germany within the last decade is the reduction of attrition rates. However, it remains unknown whether differences exist between the attrition rates and what the causes of non-completion are. Therefore, the objective of this paper is to discuss the need of a comparative empirical study to understand doctoral program attrition in both countries. This article first examines the organization of doctoral education in Germany and the USA with reference to doctoral program attrition. Secondly, it explains Bourdieu´s concept of the scientific field and the social position of doctoral students. Finally, it suggests taking a closer look at the position of doctoral students, their amount of capital and possible actions as implications for further research.